Empirical study of the relationship of the psychology of student stress and the value-semantic choice of an educational trajectory at a university - G. I. Atamanova; V. N. Romashin (Вестник университета)
The identified contradictions arisen in  the context of   geopolitical changes have led to  the need to   study the issue of  the relationship between the psychology of   stress and choice of  educational trajectory based on   the value-semantic aspect, which in   turn has become the subject of   research when choosing an   educational trajectory at a  university. The purpose is  aimed at  resolving the indicated contradictions through identifying the characteristics of   the value-semantic aspect of   students that influence their choice. The research methodology is   established on   the methods and principles that set the structure and ways to   resolve the stated contradictions in  order to  achieve the goal. Based on a   theoretical study of   the problem of   the stress influence on  humans, various approaches are considered. These approaches are meaningful for the student as  they minimise the negative impact on   their physical and mental health. They are viewed from different angles and different points of   view as a   coping strategy and stress resistance. An  empirical study of   the relationship between the psychology of   student stress and value-semantic choice of  an educational trajectory at a   university is   presented in   the dynamics of   changes of   this choice and with some statements from students confirming the conclusions formulated. In   conclusion, a  generalisation is  given and the minimum is   stated that should be   considered when choosing an   educational path based on   each participant’s own meaning and values in   order to  reduce stress in  any activity.